DESCRIPTION OF NURSE STIGMA TOWARDS PEOPLE WITH HIV/AIDS (PLWHA) - Muslimin, Ahmad (Universitas Kusuma Husada Surakarta, 2025)
Background: Stigma against people living with HIV/AIDS (PLWHA) is a serious problem due to negative perceptions. The stigma experienced causes psychological, emotional, spiritual, and social isolation, and access to health services. Nurses perpetrate one form of stigma in the healthcare environment due to a lack of knowledge, fear of HIV transmission, and misconceptions about its transmission. This study aims to investigate the perception of stigma among nurses toward people living with HIV/AIDS (PLWHA) at Tidar Hospital in Magelang City. Methods: This is a qualitative study using a case study approach. Participants were selected using purposive sampling, and the results were determined using the HIV-KQ-18 knowledge pre-test. The sample consisted of 12 informants, including nurses, PLWHA patients, ward supervisors, infection control committee members, and nursing managers. Data collection was conducted through interviews and observations from June to August 2024, and data analysis was performed using Open Code software version 4.03. Results: Stigma among nurses arises from fear and concern during patient care due to an insufficient understanding of HIV transmission and prevention. Despite exhibiting stigmatising behaviour, nurses continue to fulfil their roles and duties as caregivers. Conclusion: Stigma among nurses toward HIV/AIDS patients arises from insufficient knowledge about HIV transmission and prevention. HIV/AIDS training programs should be implemented to enhance HIV knowledge and foster positive attitudes toward HIV/AIDS patients.